2021
DOI: 10.1097/yct.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in Canada During the First Wave of COVID-19

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…Finally, it was unclear whether there was a shortage of anesthesiologists in Japan during the study period. Other countries reported that several cases of ECT were stopped due to a shortage of anesthesiologists, especially in the early stages of infection, 3 , 37 and a survey that includes the perspective of anesthesiologists is needed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, it was unclear whether there was a shortage of anesthesiologists in Japan during the study period. Other countries reported that several cases of ECT were stopped due to a shortage of anesthesiologists, especially in the early stages of infection, 3 , 37 and a survey that includes the perspective of anesthesiologists is needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The number of ECT procedures was less affected in Japan than that in several other countries. 3,4,[14][15][16] According to a previous paper from Canada, between mid-March and mid-May 2020, the number of ECT procedures in that country decreased in 64% of facilities, with procedures completely stopped in 27% of facilities. 3 In the United Kingdom and Ireland in April 2020, 88% of facilities reported a decrease in the number of ECT procedures and 24% had stopped completely, and in July 2020, 78% of facilities still reported a decrease in the number of procedures.…”
Section: Number Of Ect Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The necessity of ECT in the treatment of these illnesses was supported by professional bodies worldwide (1)(2)(3). As with most health services, and especially procedure-based services, the COVID-19 pandemic has significantly disrupted ECT services, with services across North America, Asia, Europe, and Australia reporting decreases in ECT delivery and major changes in how ECT is delivered (4)(5)(6). This qualitative study explored the experiences of ECT clinical directors and anesthetists, globally, about ECT during the pandemic, and its impact on clinical services.…”
Section: Introductionmentioning
confidence: 99%